Impact of the duration of rearing and finishing periods on steer performance and carcass and meat quality characteristics - Pavan, Enrique; Pouzo, Laura Beatriz; Testa, Maria Laura; Maglietti, Carlos Sebastian; Papaleo Mazzucco, Juliana; Pardo, Alan Maxs (Elsevier, 2023)
The present study evaluates the effects of extending the rearing period on pasture for 0, 49, and 98 d (beyond 300 kg of live weight) and of finishing on a concentrate diet for 49 and 98 d on beef carcass quality, meat and subcutaneous fat color, shear-force, fatty acid profile and on consumer sensory quality of meat. No major interactions were observed throughout the study. Increasing the rearing period increased slaughter and carcass weight and fat thickness with no other effects on meat quality. Extending the finishing period increased slaughter and carcass weight, fat thickness, and longissimus muscle area with no effects on meat color, shear-force and cooking loses. Longissimus fatty acid profile was altered by extending the finishing period with greater amounts of total FA and proportion of C18:1 cis-9 while decreasing the proportion of n-3 polyunsaturated FA. There were no effects of extending the rearing and finishing periods on consumer evaluation of sensory traits. However, evaluation of consumer clusters found greater overall and flavor liking scores for meat from steers with the shortest rearing period for Cluster-1 while Cluster-2 gave greater flavor liking scores to beef from steers where the finishing period was extended. The results suggest slaughter weight can be increased by extending the finishing period without negatively affecting consumer quality, while extending the rearing period may have a negative impact on.